Reduction of Skin pH during Treatment for Palmoplantar Hyperhidrosis: A Conjecture on the Role of pH-Regulated Water Channel, i.e. Aquaporin - Kyoko Nakahigashi; Takashi Nomura; Yoshiki Miyachi; Kenji Kabashima (Karger Publishers, 2013)
Primary palmoplantar hyperhidrosis (PPH) is a disorder that involves excessive sweating on the palms and soles. Although the pathophysiology of PPH remains unknown, some treatments, including topical aluminum chloride (AC) and tap water iontophoresis (TWI), are effective at suppressing the perspiration. Herein, we report the kinetics of the skin pH of two cases of PPH treated with AC and TWI. We found that the skin pH decreased in accordance with the reduction in sweating. This finding indicates that the reduction in sweating may be attributed to the reduction of skin pH in AC and TWI. Whether or not the pH-regulated function of aquaporin can explain this finding remains unknown.